Multiple giant pilar cyst distributed over the body since childhood - Ali Asilian; Amir Hossein Siadat; Zabiolah Shahmoradi; Sheila Shariat; Nooshin Afshar Moghadam; Hamid Soozangar (Wolters Kluwer Medknow Publications, 2016)
Trichilemmal cyst or pilar cyst is defined as a cyst containing keratin and its breakdown products. It is usually situated on the scalp with a wall resembling external hair root sheath. In this case report we present a 55-year-old man with multiple giant pilar cysts that were distributed over the whole body since childhood. One of the cyst on the chest was transformed to squamous cell carcinoma (SCC).